How Does Student’s Learning Interest in Physical Education Subject Use Nearpod Media in Covid-19 Pandemic - Fauzi, Muhammad Adnan; Subekti, Nur (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
During the COVID-19 pandemic, online learning media innovation is needed in order to maintain the obligations of educators and to create a pleasant learning atmosphere. This study aims to describe students’ learning interest in physical education-orchestral subjects using Nearpod media. In addition, it does not only describe the students’ learning interest, but also this research can be used as information media for teachers that there is the digital learning media which is ready to use. Students’ learning interest can be identified through observation done by the Program for Prospective Teachers (A learning leader who can encourage children’s development). The researcher used a qualitative descriptive design with research instruments in the form of Nearpod-based teaching materials, interview guidelines, and questionnaires. The results of this study is that the Nearpod.com learning media application can be used for learning media ‘ready-to-use’ in online learning models. It can also be developed and build an atmosphere of fun teaching and learning activities.